Masyarakat Madani dalam Perspektif Hadis - Mujahid Mujahid (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2013)
The issue of civil society or masyarakat madani has been enthusiastically discussed and associated with Islamic tradition, as the term madani itself is derived from Arabic and is regarded identical to Medina, the city in which the Prophet developed a Muslim community during his lifetime. Discussion of civil society structure becomes a choice in this description for there has been a new conception concerning the birth of a